2014
DOI: 10.1016/j.shaw.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hazards and Safety Measures Amongst the Paint Factory Workers in Lagos, Nigeria

Abstract: BackgroundThe manufacture of paint involves a variety of processes that present with medical hazards. Safety initiatives are hence introduced to limit hazard exposures and promote workplace safety. This aim of this study is to assess the use of available control measures/initiatives in selected paint factories in Lagos West Senatorial District, Nigeria.MethodsA total of 400 randomly selected paint factory workers were involved in the study. A well-structured World Health Organization standard questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
4
27
2
1
Order By: Relevance
“…Siew Lai Huang studied the particle size distribution and concentration of metallic elements of solvent-and water-based paint dust from collected bulk dust and found that the mean concentration of arsenic in solvent-based paint dust was 100 ± 0.020 mg/kg while the mean concentrations of arsenic in waterbased paint dust was 20.65 ± 6.11 mg/kg [37]. Awodele et al found that arsenic concentration in urine sample of paint factory workers was 20 times as high as that found in non-factory workers [27]. Lubricant oils are used in a variety of applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Siew Lai Huang studied the particle size distribution and concentration of metallic elements of solvent-and water-based paint dust from collected bulk dust and found that the mean concentration of arsenic in solvent-based paint dust was 100 ± 0.020 mg/kg while the mean concentrations of arsenic in waterbased paint dust was 20.65 ± 6.11 mg/kg [37]. Awodele et al found that arsenic concentration in urine sample of paint factory workers was 20 times as high as that found in non-factory workers [27]. Lubricant oils are used in a variety of applications.…”
Section: Resultsmentioning
confidence: 99%
“…The highest lead concentration was in hair specimen of a car painter (samples ID 7). Lead is one of the heavy metals contained in commonly-used raw materials in paint manufacturing as pigments or preservatives [27]. In his study, Awodele found that lead concentration in the urine of paint factory workers was twice as high as found in non-factory workers [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, paints contain pigments such as lead, cadmium, arsenic and chromium (Awodele et al 2014). Besides, Titanium dioxide and silver are nanoparticles used as paint additives (Smulders et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, (85.5%) of paint factory workers didn't use gloves, (61.5%) didn't use goggles, while (25.5%) of them used boots, and (28%) used uniform (Awodele et al, 2014). This could be attributed to an insufficient supply of PPE, lack of awareness, worker's discomfort from PPE, and lack of complying with safety rules.…”
Section: Discussionmentioning
confidence: 99%